Financial crime and knowledge workers : an empirical study of defense lawyers and white-collar criminals - Gottschalk, Petter; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2014)
Financial Crime and Knowledge Workers examines the role of lawyers in court cases involving white-collar crimes, revealing fresh insights into the relationship between a lawyer's stature and a case's potential verdict.
Keywords: White collar crimes -- Law and legislation -- Norway; Defense (Criminal procedure) -- Norway; Criminal defense lawyers -- Norway; Commercial criminals -- Norway; Knowledge management -- Norway; Criminology